Consumption of animal products in Bulgaria: The case for change - Kostova, S.; Atanasov, B.; Marinova, Dora (IGI Global, 2018)
Animal. Products. in. Bulgaria: The. Case. for. Change. Septemvrina Kostova University for National and World Economy, Bulgaria Borislav Atanasov University for National and World Economy, Bulgaria Dora Marinova Curtin University, Australia ABSTRACT This chapter analyses the trends in production and consumption of animal-based food products, including meat, dairy, eggs and fish, in Bulgaria between 2010 and 2015. Against decreasing population, the production of livestock, ...